2021
DOI: 10.1177/2150132721993631
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic as an Opportunity for Operational Innovation at 2 Student-Run Free Clinics

Abstract: The onset of the COVID-19 pandemic and subsequent county shelter-in-place order forced the Cardinal Free Clinics (CFCs), Stanford University’s 2 student-run free clinics, to close in March 2020. As student-run free clinics adhering to university-guided COVID policies, we have not been able to see patients in person since March of 2020. However, the closure of our in-person operations provided our student management team with an opportunity to innovate. In consultation with Stanford’s Telehealth team and educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Adding to previous reviews, we found reports using telemedicine to overcome the challenges in clinical education amidst the pandemic disruption ( Table 2 ). 17 papers [ 8 , 9 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ] described the use of telemedicine as an educational tool mostly for clerkship rotations but three also included pre-clinical year students. Whilst telemedicine was mainly implemented in university hospitals, six programs were also executed in the community.…”
Section: Resultsmentioning
confidence: 99%
“…5 ). Practice guidelines [ 11 , 12 , 20 , 22 ] and training for faculty and students were provided [ 10 , 14 , 16 , 18 , 20 , 22 , 24 ] prior to encountering patients over the telehealth platform. In-advance informed consent from the patients were obtained and screening took place to ensure patients had the appropriate virtual interfaces [ 18 , 19 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations